2019
DOI: 10.3390/pathogens8030145
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Newcastle Disease Virus (NDV) Expressing Sigma C Protein of Avian Reovirus (ARV) Protects against Both ARV and NDV in Chickens

Abstract: Newcastle disease (ND) and avian reovirus (ARV) infections are a serious threat to the poultry industry, which causes heavy economic losses. The mesogenic NDV strain R2B is commonly used as a booster vaccine in many Asian countries to control the disease. In this seminal work, a recombinant NDV strain R2B expressing the sigma C (σC) gene of ARV (rNDV-R2B-σC) was generated by reverse genetics, characterized in vitro and tested as a bivalent vaccine candidate in chickens. The recombinant rNDV-R2B-σC virus was at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 43 publications
1
17
0
Order By: Relevance
“…The cells were then blocked with 5% bovine serum albumin for 30 min at room temperature. They were washed three times with PBS and incubated for 1 h with a mixture of anti-NDV and anti-CIAV primary antibodies, as mentioned previously [ 9 ]. At the end of incubation period, cells were washed thrice with PBS and incubated with a mixture of FITC labelled rabbit anti-chicken IgG and Alexa Fluor 568 labelled goat anti-chicken IgG and kept for one hour at room temperature.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The cells were then blocked with 5% bovine serum albumin for 30 min at room temperature. They were washed three times with PBS and incubated for 1 h with a mixture of anti-NDV and anti-CIAV primary antibodies, as mentioned previously [ 9 ]. At the end of incubation period, cells were washed thrice with PBS and incubated with a mixture of FITC labelled rabbit anti-chicken IgG and Alexa Fluor 568 labelled goat anti-chicken IgG and kept for one hour at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…At the end of incubation period, cells were washed thrice with PBS and incubated with a mixture of FITC labelled rabbit anti-chicken IgG and Alexa Fluor 568 labelled goat anti-chicken IgG and kept for one hour at room temperature. Nucleus staining was performed using DAPI at 1:1000 dilution and finally the cells were visualised for corresponding fluorescence a images were taken using Fluoview FV 1000 confocal microscope (Olympus, Tokyo, Japan) at the matching excitation and emission filters for FITC and Alexa Fluor 568, as described [ 9 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…NDV has been used as a vector for vaccine development since the late 1990s. The efficiency of vaccines based on this vector has been demonstrated against respiratory viruses, in chickens against infectious bronchitis virus and avian reovirus, in monkeys against SARS-CoV and in camels against MERS-CoV [33][34][35][36] . These studies have demonstrated that it is feasible to produce S protein from other viruses, especially of SARS-CoV and MERS, which conferred strong immunogenicity and protection in mice and nonhumans primates 35,36 .…”
mentioning
confidence: 99%